Implementasi Promosi Kesehatan dan Edukasi Pola Makan pada Asuhan Keperawatan Pasien Gastritis - Adelia Bekti Widyaningrum; Afrian Yohans Fernandho; Alifia Fara Yuliananda; Della Nur’Aini; Fitriana Amalia Al Wafi; Genovia Judit De Carvalho Lake Guterres; Siska Anggraini Yudha Pertiwi; Liss Dyah Dewi Arini (INDO PUBLISHING, 2025)
Gastritis is a digestive system disorder often triggered by irregular eating patterns and inadequate intake, making the stomach more sensitive to stomach acid. The prevalence of gastritis in Indonesia is quite high, with the incidence reaching 40.8% according to the WHO, and several regions reporting thousands of cases. The first study showed a significant association between diet and the incidence of gastritis, while health promotion did not prove a direct relationship. The second study emphasized the importance of implementing nursing care with a focus on meeting the patient's basic needs, particularly pain, nutritional changes, and the risk of fluid volume deficiency. Case studies revealed that stress, inappropriate diet, and food consumption habits can exacerbate gastritis symptoms, but structured nursing interventions can effectively address these issues. The third study highlighted the role of health education and counseling in increasing public knowledge, particularly students, about digestive system diseases such as gastritis and appendicitis. Results showed a significant increase in students' knowledge after counseling, which supports prevention through healthy lifestyle practices. Overall, the findings emphasize the importance of good diet, appropriate nursing interventions, and health education as key strategies in the management and prevention of gastritis.